Emprendimiento cultural en Colima.Generación de modelos de negocio para el desarrollo de la economía creativa local - Márquez Orozco, Liliana (Editorial Uniagustiniana, 2018)
This research aims to know the importance of cultural entrepreneurship in Colima and the relevance of found-ing a consulting agency in the field of culture. There-fore, the present chapter describes the problem, the objective of the study and its analysis and observation units, and explains the designed method used to gather information. Later, the authors share some significant results and the main conclusions of the study. The mul-tidisciplinary focus favored the articulation of knowl-edge in relation to the field of cultural management, management sciences, and marketing.